Laparoscopy for the Treatment of Congenital Hernia: Use of Surgical Meshes and Mesenchymal Stem Cells in a Clinically Relevant Animal Model - Marinaro, Federica; Casado, Javier G.; Blázquez, Rebeca; Brun, Mauricio Veloso; Marcos, Ricardo; Santos, Marta; Duque, Francisco Javier; López, Esther; Álvarez, Verónica; Usón, Alejandra; Sánchez-Margallo, Francisco Miguel (Frontiers in Pharmacology, 2020)
More than a century has passed since the first surgical mesh for hernia repair was developed, and, to date, this is still the most widely used method despite the great number of complications it poses. The purpose of this study was to combine stem cell therapy and laparoscopy for the treatment of congenital hernia in a swine animal model. Porcine bone marrow-derived mesenchymal stem cells (MSCs) were seeded on polypropylene surgical meshes using a fibrin sealant solution as a vehicle. Meshes with (cell group) or without (control group) MSCs were implanted through laparoscopy in Large White pigs with congenital abdominal hernia after the approximation of hernia borders (implantation day). A successive laparoscopic biopsy of the mesh and its surrounding tissues was performed a week after implantation, and surgical meshes were excised a month after implantation. Ultrasonography was used to measure hernia sizes. Flow cytometry, histological, and gene expression analyses of the biopsy and necropsy samples were performed. The fibrin sealant solution was easy to prepare and preserved the viability of MSCs in the surgical meshes. Ultrasonography demonstrated a significant reduction in hernia size 1 week after implantation in the cell group relative to that on the day of implantation (p < 0.05). Flow cytometry of the mesh-infiltrated cells showed a non-significant increase of M2 macrophages when the cell group was compared with the control group 1 week after implantation. A significant decrease in the gene expression of VEGF and a significant increase in TNF expression were determined in the cell group 1 month after implantation compared with gene expressions in the control group (p < 0.05). Here, we propose an easy and feasible method to combine stem cell therapy and minimally invasive surgical techniques for hernia repair. In this study, stem cell therapy did not show a great immunomodulatory or regenerative effect in overcoming hernia-related complications. However, our clinically relevant animal model with congenital hernia closely resembles the clinical human condition. Further studies should be focused on this valuable animal model to evaluate stem cell therapies in hernia surgery.